Damp housing and childhood asthma: validation of reporting of symptoms. Issue 6658 (12th November 1988) - Strachan, D. P.
Abstract : The relations among parental reports of respiratory symptoms, bronchospasm measured after exercise, and the presence of visible fungal mould in the home was assessed in a population sample of 7 year old children (n = 873). Wheeze in the past year was the symptom most closely associated with reported dampness and particularly with mould. The unadjusted odds ratio relating mould and wheeze was 3.70 (95% confidence interval 2.22 to 6.15), and after adjustment for housing tenure, number of people per room, number of smokers in the household, and gas cooking this remained highly significant (odds ratio 3.00 (1.72 to 5.25)). The reduction in forced expiratory volume in one second after six minutes of free running was used to validate reporting of wheeze. At all levels of measured bronchial lability wheeze was reported more commonly in the children from homes with mould. There was no significant difference in the degree of bronchospasm measured among children from homes with and without mould. Awareness of dampness or mould in the home may be a determinant of parental reporting of symptoms and may account for much of the observed association between mould and respiratory symptoms.